2019
DOI: 10.1002/jcp.28997
|View full text |Cite
|
Sign up to set email alerts
|

Laminin‐derived peptide C16 regulates Tks expression and reactive oxygen species generation in human prostate cancer cells

Abstract: Laminin peptides influence cancer biology. We investigated the role of a lamininderived peptide C16 regulating invadopodia molecules in human prostate cancer cells (DU145). C16 augmented invadopodia activity of DU145 cells, and stimulated expression Tks4, Tks5, cortactin, and membrane-type matrix metalloproteinase 1.Reactive oxygen species generation is also related to invadopodia formation. This prompted us to address whether C16 would induce reactive oxygen species generation in DU145 cells. Quantitative flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…A contribution of Tks4 to cancer progression has been suggested in several cancer types, including breast cancer [53], melanoma [27], acute myeloid leukemia [54], and prostate cancer [55]. Consistent with these links, a detailed analysis showed that Tks4 and its phosphorylation are implicated in invadopodia formation in human colon cancer cells [56].…”
Section: Discussionmentioning
confidence: 85%
“…A contribution of Tks4 to cancer progression has been suggested in several cancer types, including breast cancer [53], melanoma [27], acute myeloid leukemia [54], and prostate cancer [55]. Consistent with these links, a detailed analysis showed that Tks4 and its phosphorylation are implicated in invadopodia formation in human colon cancer cells [56].…”
Section: Discussionmentioning
confidence: 85%
“…It was suspected that TKS proteins, which are members of the same family, can also play regulatory roles in channeling and localizing the NOX enzymes to the podosome/invadopodium membrane to locally increase the ROS concentration [65,146]. TKS5 has been shown to colocalize with ROS [147]. Furthermore, Diaz et al…”
Section: The Possible Role Of Tks4 and Tks5 In The Compartmentalization Of Oxidative Processesmentioning
confidence: 99%
“…Prostate cancer remains a major cause of mortality annually among males [1][2][3][4][5][6]. In 2015, prostate cancer was the fifth commonly diagnosed cancer in South Korea and it is expected to become the fourth in 2019 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%